Atos de prazer: o Grupo Palco & Rua e o teatro amador na cidade de Ouro Preto - 1976 a 2012 - Flaviano Souza e Silva (2013)
This work presents an overview of the amateur theatre in Brazil between the 17th and 21st centuries and in the city of Belo Horizonte (Minas Gerais, Brazil) between the 20th and 21st centuries. It discusses pleasure as a motivational force for amateur theatre and detects common characteristics of Brazilian amateur groups. It also exposes elements of artistic connection between the cities of Belo Horizonte and Ouro Preto and identifies theatrical events and amateur groups which are important to understanding theatre in the city of Ouro Preto in the period between 1976 and 2012. Finally, the amateur theatre group from Ouro Preto, Palco & Rua, is taken as object of study, having its history and most striking features presented.